Memory in Motion : Archives, Technology, and the Social - Lundemo, Trond; Blom, Ina; Rossaak, Eivind (Book collections on Project MUSE., 2017)
How should we understand social memory in the age of new media? Classic sociology described the ways in which social memory was enacted through ritual, language art, architecture and institution - phenomena whose persistence over time and whose capacity for a shared storing of the past was contrasted with fleeting individual memory. Society is memory, Émile Durkheim stated. However, today's new time technologies compel us to rethink this concept of memory and its emphasis on a shared past. For in the age of digital computing, instant updating and transfer functions and interconnection through real time networks give an unprecedented priority to the present and the future, while challenging the very distinction between individual and collective memory. New media technologies raise the question of the temporalities of memory to a principle, challenging not just the classic description of social memory, but also the social ontology that it presupposes. 'Memory in Motion: Archives, Technology and the Social' discusses the new technologies of memory from perspectives that explicitly investigate their impact on the very conceptualization of the social.